Pattern of access determines influence of junk food diet on cue sensitivity and palatability. (1st April 2018) - Kosheleff, Alisa R.; Araki, Jingwen; Hsueh, Jennifer; Le, Andrew; Quizon, Kevin; Ostlund, Sean B.; Maidment, Nigel T.; Murphy, Niall P.
Abstract: Aims: Like drug addiction, cues associated with palatable foods can trigger food-seeking, even when sated. However, whether susceptibility to the motivating influence of food-related cues is a predisposing factor in overeating or a consequence of poor diet is difficult to determine in humans. Using a rodent model, we explored whether a highly palatable 'junk food' diet impacts responses to reward-paired cues in a Pavlovian-to-instrumental transfer test, using sweetened condensed milk (SCM) as the reward. The hedonic impact of SCM consumption was also assessed by analyzing licking microstructure. Methods: To probe the effects of pattern and duration of junk food exposure, we provided rats with either regular chow ad libitum (controls) or chow plus access to junk food for either 2 or 24 h per day for 1, 3, or 6 weeks. We also examined how individual susceptibility to weight gain related to these measures. Results: Rats provided 24 h access to the junk food diet were insensitive to the motivational effects of a SCM-paired cue when tested sated even though their hedonic experience upon reward consumption was similar to controls. In contrast, rats provided restricted, 2 h access to junk food exhibited a cue generalization phenotype under sated conditions, lever-pressing with increased vigor in response to both a SCM-paired cue, and a cue not previously paired with reward. Hedonic response was also significantly higher in these animals relative to controls. Conclusions: These data demonstrate that the pattern of junk food exposure differentially alters the hedonic impact of palatable foods and susceptibility to the motivating influence of cues in the environment to promote food-seeking actions when sated, which may be consequential for understanding overeating and obesity.